Pelaksanaan Kegiatan P5 Kurikulum Merdeka Di SD Marsudirini Gedangan Semarang - Andarweni Astuti; Ambrosius Heri Krismawanto (Publisher STPKat, 2023)
The Ministry of Education and Culture in 2022 presents challenges in the education sector. The problem was solved by the government by making the Freedom to Learn Program policy. The purpose of this study: to analyze the time allocation and the theme of the choice of implementation of the P5 independent curriculum and to analyze the principles, benefits, design implementation and management strategy of the P5 independent curriculum at SD Marsudirini Gedangan, Semarang. The method is qualitative with a case study approach, research data uses primary data, data collection techniques by observation, observation, recording observations, and structured interviews, data validity techniques by triangulation of data sources. The findings are that the independent learning curriculum is quite fun and does not make it difficult for teachers and students at SD Marsudirini Gedangan. Uncertainty was felt when the teachers did not know the process for implementing the main harvest in December 2022 and there was no BOS allocation fund to support project implementation. The implication of this research is to provide an overview of the implementation of a fun independent learning curriculum, so that in the 2023/2024 academic year schools are increasingly ready to implement the full learning independent curriculum